THE UTILIZATION OF THE ELSA SPEAK APPLICATION AS A LEARNING MEDIUM TO IMPROVE PRONUNCIATION AND ENGLISH SPEAKING SKILLS AMONG STUDENTS - Afni Rosalina (Universitas Ubudiyah Indonesia, 2025)
ABSTRACT The ability to speak in English is one of the important skills that students must possess in the era of globalization. However, many students still face challenges in pronunciation and fluency. This study aims to analyze the effectiveness of utilizing an artificial intelligence-based application, namely Elsa Speak, in improving students' pronunciation and speaking skills. The method used is a quasi-experimental design with a one group pre-test and post-test approach. The research subjects were students of the English Education study program who underwent training using the Elsa Speak application for one week. The instruments used include a speaking test and a pronunciation assessment rubric. The research results show a significant improvement in pronunciation and speaking skills after using the Elsa Speak application. Thus, this application is effective as an alternative learning medium in teaching English speaking skills independently and interactively. Keywords: Elsa Speak, speaking, pronunciation, artificial intelligence, learning media